FUKUSHIMA DAI-ICHI ACCIDENT: LESSONS LEARNED AND FUTURE ACTIONS FROM THE RISK PERSPECTIVES - JOON-EON YANG (Nuclear Engineering and Technology, 2014)
The Fukushima Dai-Ichi accident in 2011 has affected various aspects of the nuclear society worldwide. The accident revealed some problems in the conventional approaches used to ensure the safety of nuclear installations. To prevent such disastrous accidents in the future, we have to learn from them and improve the conventional approaches in a more systematic manner. In this paper, we will cover three issues. The first is to identify the key issues that affected the progress of the Fukushima Dai-Ichi accident greatly. We examine the accident from a defense-in-depth point of view to identify such issues. The second is to develop a more systematic approach to enhance the safety of nuclear installations. We reexamine nuclear safety from a risk point of view. We use the concepts of residual and unknown risks in classifying the risk space. All possible accident scenarios types are reviewed to clarify the characteristics of the identified issues. An approach is proposed to improve our conventional approaches used to ensure nuclear safety including the design of safety features and the safety assessments from a risk point of view. Finally, we address some issues to be improved in the conventional risk assessment and management framework and/or practices to enhance nuclear safety.